2016
DOI: 10.1016/j.dsi.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Circulating endothelial cells and serum visfatin are indicators of cardiovascular disease risk in psoriasis patients

Abstract: a b s t r a c tBackground: Cardiovascular risk in psoriasis (PS) appears to be dependent on disease severity. Circulating endothelial cell (CEC) counts appear to be elevated in numerous conditions associated with endothelial dysfunction including chronic immune-mediated inflammatory disorders. Adipokines could serve as a missing link between PS and comorbidities Aim: To evaluate the numbers of CECs and serum visfatin levels in PS patients in comparison to controls to investigate their possible role in increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…18,19,23,24,[26][27][28][29][30][31][32] The pooled results demonstrated that visfatin levels were significantly higher in the psoriasis group than in the control group (SMD ¼ 0.90, 95% CI 0.52, 1.28, P < 0.001) (Figure 2). 18,19,23,24,[26][27][28][29][30][31][32] Cochran's Q test showed significant heterogeneity among these included studies (I 2 ¼ 84.2%, P < 0.001). Subgroup analyses were performed due to the existence of heterogeneity.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…18,19,23,24,[26][27][28][29][30][31][32] The pooled results demonstrated that visfatin levels were significantly higher in the psoriasis group than in the control group (SMD ¼ 0.90, 95% CI 0.52, 1.28, P < 0.001) (Figure 2). 18,19,23,24,[26][27][28][29][30][31][32] Cochran's Q test showed significant heterogeneity among these included studies (I 2 ¼ 84.2%, P < 0.001). Subgroup analyses were performed due to the existence of heterogeneity.…”
Section: Resultsmentioning
confidence: 98%
“…As shown in Figure 1, a total of 11 casecontrol studies were eligible to be included in the meta-analysis, with 448 patients with psoriasis and 377 controls. 18,19,23,24,[26][27][28][29][30][31][32] These studies were published from 2012 to 2020 and were undertaken in Asia, Africa and Europe. In the study quality assessment, 10 studies had a NOS score !7.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations